2011
DOI: 10.4236/ojdm.2011.12012
|View full text |Cite
|
Sign up to set email alerts
|

Word-Representability of Line Graphs

Abstract: A graph <i>G</i>=(<i>V,E</i>) is representable if there exists a word <i>W</i> over the alphabet <i>V</i> such that letters <i>x</i> and <i>y</i> alternate in <i>W</i> if and only if (<i>x</i> ,<i>y</i>) is in <i>E</i> for each <i>x</i> not equal to <i>y</i> . The motivation to study representable graphs came from algebra, but this subject is interesting from graph the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 4 publications
(5 reference statements)
0
30
0
Order By: Relevance
“…V m−1 and V 0 ). For example, referring to Figure 2.4, the layer L 2 is the induced subgraph formed by the vertices {v 10 , v 11 , v 12 , v 13 , v 20 , v 21 , v 22 , v 23 }, while the sector S 3 is the induced subgraph formed by the vertices {v 02 , v 12 , v 22 , v 03 , v 13 , v 23 }.…”
Section: Grid-covered Cylinder Graphsmentioning
confidence: 99%
“…V m−1 and V 0 ). For example, referring to Figure 2.4, the layer L 2 is the induced subgraph formed by the vertices {v 10 , v 11 , v 12 , v 13 , v 20 , v 21 , v 22 , v 23 }, while the sector S 3 is the induced subgraph formed by the vertices {v 02 , v 12 , v 22 , v 03 , v 13 , v 23 }.…”
Section: Grid-covered Cylinder Graphsmentioning
confidence: 99%
“…For example, the cycle graph on 4 vertices labeled by 1, 2, 3 and 4 in clockwise direction can be represented by the word 14213243. There is a long line of research on word-representable graphs [1]- [8], and the current paper is a continuation of this line of research. A comprehensive introduction to the theory of word-representable graphs will be given in [5].…”
Section: Introductionmentioning
confidence: 97%
“…Recently, a number of (fundamental) results on word-representable graphs were obtained in the literature; for example, see [1], [3], [5], [7], [9], [11], and [12]. In particular, Halldórsson et al [7] have shown that a graph is wordrepresentable if and only if it admits a semi-transitive orientation (to be defined in Section 2), which, among other important corollaries, implies that all 3-colorable graphs are word-representable.…”
Section: Introductionmentioning
confidence: 99%